Small-molecule inhibitors of protein-protein interactions - Vassilev, Lyubomir; aFry, David (Springer Berlin Heidelberg, 2011)
abody> In this volume, the editors have collected the knowledgeable insights of a number of leaders in this field - researchers who have achieved success in addressing the difficult problem of inhibiting protein-protein interactions. These researchers describe their unique approaches, and share experiences, results, thoughts, and opinions. The content of the articles is rich, and in terms of scope ranges from generalized approaches to specific case studies. There are various focal points, including methodologies and the molecules themselves. Ultimately, there are numerous lessons to be taken away from this collection, and the editors hope that this snapshot of the current state of the art in developing protein-protein inhibitors not only pays tribute to the past successes, but also generates excitement about the future potential of this field.